Antihyperglycemic and Antihyperlipidemic Effects of Aqueous Extracts of Lannea edulis in Alloxan-Induced Diabetic Rats - Banda, Michelo; Nyirenda, James; Muzandu, Kaampwe; Sijumbila, Gibson; Mudenda, Steward (Frontiers in Pharmacology, 2018)
Lannea edulis (Sond.) Engl. commonly known as wild grape is used traditionally for the treatment of diabetes. It is only found in Eastern and Southern Africa. We carried out phytochemical screening, and determined the antihyperglycemic and antihyperlipidemic effects of an aqueous extract of L. edulis in alloxan induced diabetic rats. We report herein the findings of this research work.L. edulis crude aqueous extract was obtained by hot infusion and evaporation method. Phytochemical screening was carried out and subsequently toxicity studies were performed to establish the Lethal Dose 50 (LD50) in albino rats. Alloxan monohydrate was used to induce diabetes in the rats. L. edulis doses were administered to treatment groups for 14 days. Blood was drawn on days 0, 1, 3, 5 7 and 14 for fasting blood glucose and days 0 and 14 for the determination of lipids. Phytochemical screening revealed the presence of flavonoids, saponins, tannins, cardiac glycosides, alkaloids and steroids. L. edulis treatment groups showed significant (P<0.05) dose dependent reductions in fasting blood glucose levels. When day 0 mean blood glucose levels were compared to day 3 mean blood glucose levels of their respective groups, the 300 mg/kg L. edulis group showed a 23.3 percent drop and the 500 mg/kg L. edulis group showed a 52.6 percent drop. The 100 mg/kg L. edulis treatment group showed a 25.1 percent drop by day 5, the day on which it showed statistical significance (P<0.05) compared to the diabetic control. In addition, administration of aqueous extract of L. edulis to diabetic rats for 14 days significantly decreased (P<0.05) the levels of serum total cholesterol, triglycerides, Low Density Lipoprotein (LDL) and Very Low Density Lipoprotein (VLDL) whilst increasing the levels of High Density Lipoprotein (HDL), when compared to the diabetic control group. It was concluded that L. edulis showed significant and dose dependent antihyperglycemic and antihyperlipidemic effects thus confirming its traditional use.